Analyticity of the streamlines and of the free surface for periodic equatorial gravity water flows with vorticity. (February 2015) - Martin, Calin Iulian
Abstract: We prove analyticity of the streamlines beneath the surface and the smoothness of the free surface for geophysical equatorial water flows with a general Hölder continuously differentiable underlying vorticity distribution under the assumption of no stagnation points in the flow. Moreover, we prove that the real-analyticity of the vorticity function implies the real-analyticity of the free surface.